2005
DOI: 10.1007/s11252-005-1422-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical and physical propertiesof stream water across an urban-rural gradient in western Georgia

Abstract: The Middle Chattahoochee River Watershed in western Georgia is undergoing rapid urban development. Consequently, Georgia's water quality is threatened by extensive development as well as other land uses such as grazing. Maintenance of stream water quality, as land development occurs, is critical for the protection of drinking water, biotic integrity, and stream morphology. A two-phase, watershed-scale study was established to develop relationships among land use and water quality within western Georgia. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
6
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 36 publications
9
71
6
2
Order By: Relevance
“…Similarly, residues created by human activities have diffuse effects on water bodies and are associated with surface runoff in catchment areas. Nutrient concentration in watersheds with impervious surface above 5% often exceeds that of other watersheds during both baseflow and stormflow (Schoonover et al, 2005). According to Alberti (2005), high nutrient concentration, which is frequently observed in urban drainage areas, creates unsuitable conditions for some fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, residues created by human activities have diffuse effects on water bodies and are associated with surface runoff in catchment areas. Nutrient concentration in watersheds with impervious surface above 5% often exceeds that of other watersheds during both baseflow and stormflow (Schoonover et al, 2005). According to Alberti (2005), high nutrient concentration, which is frequently observed in urban drainage areas, creates unsuitable conditions for some fish species.…”
Section: Discussionmentioning
confidence: 99%
“…The author speculated that shallow groundwater chemistry in the region may have been influenced by effluent contamination originating from numerous septic tank systems and leaky underground sewer pipes. Schoonover et al (2005) also found elevated levels of chloride, nitrate, sulfate, TDS, potassium and sodium in baseflows derived from watersheds with greater than 5% TIA in western GA [42].…”
Section: Urbanization Effects On Water Qualitymentioning
confidence: 92%
“…Urbanization increases impervious area, resulting in quicker and larger pulses in storm flow, geomorphic changes in stream channels, and higher sediment yields (Arnold et al, 1982;Wahl et al, 1997). Urban lands are also potential sources for heavy metals, nutrients, and bacteria (Rose, 2002;Schoonover et al, 2005). Excessive loads of nitrogen (N) and phosphorus (P) in urban streams can trigger undesirable effects in the receiving water bodies, such as algal blooms, eutrophication, and hypoxia.…”
Section: Introductionmentioning
confidence: 99%